Analysis of the Influence of CPEC on Monetary Policy Decision in Pakistan - Sanghro, Majid Ali; Khaskhelly, Farhanzeb; Khashkelly, Ambreen Zeb (Progressive Research Journal of Arts & Humanities (PRJAH), 2020)
The purpose of this research is to extent to which the China- Pakistan Economic Corridor (CPEC) can impact monetary policy decisions in Pakistan. This is in response to further research in previous studies. A robust econometric model was applied to economic data procured from the financial and statistical institutions in Pakistan and China. The analysis suggests the potential of the economic cooperation to inure to the benefit of both Pakistan and China in terms of economic development. Return on the analysis indicated that financial sector in Pakistan in particular is more susceptible to risk based on the influx of Chinese funds into the system. Specifically it is concluded the inflation and foreign exchange volatility are the most vulnerable areas of concern. Based on this knowledge it is proposed that the financial regulatory authorities in Pakistan must develop appropriate response strategies to safeguard the stability of the entire financial system on a constant basis.